(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
The study aimed to assess the sanitary facilities and practices of public schools in Nepalgunj Sub Metropolitan. The study used a descriptive research design based on primary data from questionnaires. The data were analyzed using percentage and frequency tables. The results showed that the schools had concrete boundary walls, but lacked gardens and playgrounds. The water supply was adequate, but the purification was poor. Only 20% of the schools used purified water. The toilets were satisfactory, but 80% of them had no facilities inside. The waste disposal was haphazard and unmanaged. Only 20% of the schools cleaned their surroundings and classrooms daily. The study concluded that the sanitary facilities and practices were satisfactory, but not well managed. The schools had no plans or ideas for improving their physical plant. The study recommended that the government should include regular programs on sanitation in the curriculum and the schools should implement them properly.